Comorbid Heart Disease in Patients with COPD is Associated with Increased Hospitalization and Mortality – A 15-Year Follow-Up - Giezeman M; Sundh J; Athlin Å; Lisspers K; Ställberg B; Janson C; Montgomery S; Kisiel MA; Nager A; Sandelowsky H; Hasselgren M (International Journal of COPD, 2023)
Maaike Giezeman,1,2 Josefin Sundh,3 Åsa Athlin,1 Karin Lisspers,4 Björn Ställberg,4 Christer Janson,5 Scott Montgomery,6– 8 Marta A Kisiel,9 Anna Nager,10 Hanna Sandelowsky,7,10,11 Mikael Hasselgren1,2 1School of Medical Sciences, Faculty of Medicine and Health, Örebro University, Örebro, Sweden; 2Centre for Clinical Research and Education, Karlstad, Sweden; 3Department of Respiratory Medicine, School of Medical Sciences, Faculty of Medicine and Health, Örebro University, Örebro, Sweden; 4Department of Public Health and Caring Sciences, Family Medicine and Preventive Medicine, Uppsala University, Uppsala, Sweden; 5Department of Medical Sciences, Respiratory, Allergy & Sleep Research, Uppsala University, Uppsala, Sweden; 6Clinical Epidemiology and Biostatistics, School of Medical Sciences, Faculty of Medicine and Health, Örebro University, Örebro, Sweden; 7Clinical Epidemiology Division, Department of Medicine, Solna, Karolinska Institutet, Stockholm, Sweden; 8Department of Epidemiology and Public Health, University College London, London, UK; 9Department of Medical Sciences, Occupational and Environmental Medicine, Uppsala University, Uppsala, Sweden; 10Division of Family Medicine and Primary Care, Inst NVS, Karolinska Institutet, Stockholm, Sweden; 11Academic Primary Health Care Centre, Region Stockholm, SwedenCorrespondence: Maaike Giezeman, School of Medical Sciences, Faculty of Medicine and Health, Örebro University, Örebro, Sweden, Email Maaike.giezeman@oru.sePurpose: The aim of this study was to examine the association of comorbid heart disease, defined as chronic heart failure or ischemic heart disease, on all-cause and cause-specific hospitalization and mortality in patients with COPD over a period of nearly 15 years.Materials and Methods: The cohort study included patients with COPD from primary and secondary care in 2005 with data from questionnaires and medical record reviews. The Swedish Board of Health and Welfare provided hospitalization and mortality data from 2005 through 2019. Cox regression analyses, adjusted for sex, age, educational level, smoking status, BMI, exacerbations, dyspnea score and comorbid diabetes or hypertension, assessed the association of comorbid heart disease with all-cause and cause-specific time to first hospitalization and death. Linear regression analyses, adjusted for the same variables, assessed this association with hospitalization days per year for those patients that had been hospitalized.Results: Of the 1071 patients, 262 (25%) had heart disease at baseline. Cox regression analysis showed a higher risk of hospitalization for patients with heart disease for all-cause (HR (95% CI) 1.55; 1.32– 1.82), cardiovascular (2.14; 1.70– 2.70) and other causes (1.27; 1.06– 1.52). Patients with heart disease also had an increased risk of all-cause (1.77; 1.48– 2.12), cardiovascular (3.40; 2.41– 4.78) and other (1.50; 1.09– 2.06) mortality. Heart disease was significantly associated with more hospitalization days per year of all-cause (regression coefficient 0.37; 95% CI 0.15– 0.59), cardiovascular (0.57; 0.27– 0.86) and other (0.37; 0.12– 0.62) causes. No significant associations were found between heart disease and respiratory causes of hospitalization and death.Conclusion: Comorbid heart disease in patients with COPD is associated with an increased risk for all-cause hospitalization and mortality, mainly due to an increase of hospitalization and death of cardiovascular and other causes, but not because of respiratory disease. This finding advocates the need of a strong clinical focus on primary and secondary prevention of cardiovascular disease in patients with COPD.Keywords: chronic obstructive pulmonary disease, comorbidity, chronic heart failure, ischemic heart disease, hospitalization, mortality